Adopsi Financial Technology Dan Implikasinya Terhadap Literasi Keuangan Di Kalangan Gen Z - Hastuty Hs, Widy; Hou, Amin; Rivai, Ahmad; Windi Ayuni, Tyus; Harianto, Adi (JURNAL EKUIVALENSI, 2024)
Advancements in information technology, heightened utilization of digital devices, and the demand for more efficient financial services have elevated Financial Technology (FinTech) to prominence within the financial industry. Due to the extensive utilization of smartphones and internet access, Generation Z depends on FinTech applications for financial requirements, including expenditure management, investment, and everyday transactions. The millennial generation has a predisposition for digital solutions due to their simplicity, adaptability, and rapidity of service. Consequently, it is crucial to comprehend the degree to which FinTech adoption enhances Gen Z's financial literacy. This study examines the correlation between FinTech utilization and enhanced financial literacy as a means to cultivate a financially astute generation in the digital age. This research utilized a quantitative methodology and comprised 100 Gen Z participants residing in Medan City, as established using the Slovin formula. The findings indicate that FinTech positively and significantly influences Gen Z's financial literacy, evidenced by a coefficient of determination (R²) of 0.722, or 72%. FinTech accounts for 72% of the variance in financial literacy among Gen Z, with other unexamined factors affecting the remaining 28%.